CIVIL PROCEDURE AND ECTHR JURISPRUDENCE: ECONOMIC IMPLICATIONS AND AZERBAIJAN’S EXPERIENCE - Nurzhan Maxatov; Margulan Bekturganov; Nataliia Petrenko (Baltic Journal of Economic Studies)
This article examines the economic implications of European Court of Human Rights (ECtHR) jurisprudence on civil procedural law, focusing on Azerbaijan as a case study. The study explores how ECtHR decisions have influenced legislative reforms and judicial practice in Azerbaijan, and analyzes the effects on economic efficiency, investment attractiveness, financial costs, and the stability of the legal framework. Since joining the Council of Europe and adopting the European Convention on Human Rights (ECHR), Azerbaijan has undertaken numerous judicial reforms to align its civil procedure with European standards. These efforts have focused on reducing case backlogs, ensuring the timely enforcement of court decisions, and enhancing judicial independence, all of which have a direct impact on the country's business environment. The study reviews significant ECtHR cases involving Azerbaijan, evaluates reform measures (such as the introduction of specialised commercial courts, simplified proceedings for minor claims, and alternative dispute resolution mechanisms), and discusses their economic impacts. The findings indicate that while reforms inspired by ECtHR principles have improved Azerbaijan's judicial efficiency and international image (as reflected in improved ease-of-doing-business rankings), challenges such as inconsistent application of ECtHR case law, corruption, and incomplete implementation of judgments continue to undermine the full economic benefits. It is therefore essential for the country to pursue further harmonisation with ECtHR standards and strengthening the rule of law if it is to enhance investor confidence and sustainable economic development.